2001
DOI: 10.1093/carcin/22.3.433
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and aldehyde dehydrogenase gene polymorphisms and oropharyngolaryngeal, esophageal and stomach cancers in Japanese alcoholics

Abstract: Alcohol dehydrogenase-2 (ADH2) and aldehyde dehydrogenase-2 (ALDH2) gene polymorphisms play roles in ethanol metabolism, drinking behavior and esophageal carcinogenesis in Japanese; however, the combined influence of ADH2 and ALDH2 genotypes on other aerodigestive tract cancers have not been investigated. ADH2/ALDH2 genotyping was performed on lymphocyte DNA samples from Japanese alcoholic men (526 cancer-free; 159 with solitary or multiple aerodigestive tract cancers, including 33 oropharyngolaryngeal, 112 es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
202
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(218 citation statements)
references
References 33 publications
11
202
1
2
Order By: Relevance
“…Previous case-control studies 20,21 showed consistently positive associations of the ALDH2*1/*2 genotype with the risk for esophageal cancer in East Asian heavy drinkers, and this enzyme-related vulnerability may extend to light to moderate drinkers. Several studies 20,22 also suggest similar associations with the risk of head and neck cancer in Japanese moderate to heavy drinkers.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Previous case-control studies 20,21 showed consistently positive associations of the ALDH2*1/*2 genotype with the risk for esophageal cancer in East Asian heavy drinkers, and this enzyme-related vulnerability may extend to light to moderate drinkers. Several studies 20,22 also suggest similar associations with the risk of head and neck cancer in Japanese moderate to heavy drinkers.…”
mentioning
confidence: 79%
“…Several studies 20,22 also suggest similar associations with the risk of head and neck cancer in Japanese moderate to heavy drinkers. Although some researchers studied the possible associations between these polymorphisms and HCC, [23][24][25][26] the results have been inconsistent.…”
mentioning
confidence: 79%
“…The PCR products were digested overnight with MaeIII and MboII for ADH1B and ALDH2, respectively. 8,9 Protocols were recently introduced that allow PCR amplification from whole blood or dried blood spotted on filter paper without DNA extraction. [10][11][12][13][14][15] Here, we describe a simplified and rapid PCR-RFLP assay that can be performed on blood dried on paper.…”
Section: Introductionmentioning
confidence: 99%
“…1 The inactive heterozygous aldehyde dehydrogenase-2 (ALDH2) encoded by ALDH2*1/*2 and the less-active alcohol-dehydrogenase-1B (ADH1B, previously called ADH2) encoded by ADH1B*1/*1 increase the risk of SCC in the UADT in Japanese alcoholic men 2,3 and East Asian drinking populations. [4][5][6] Most homozygotes for inactive ALDH2 are nondrinkers or occasional drinkers, because they experience severe acetaldehydemia and very unpleasant flushing responses, 4 and East Asians with active ALDH2 or ADH1B*1/*1 are at high risk of developing alcoholism.…”
mentioning
confidence: 99%